Allelopathy Test of Reeds (Imperata cylindrica) on Germination and Early Growth of Green Beans (Vigna radiata L): Uji Alelopati Alang-Alang (Imperata cylindrica) Pada Perkecambahan Dan Pertumbuhan Awal Kacang Hijau (Vigna radiata L) - Susilo, Bagas Sadam Mas; Indarwati, Indarwati; Susilo, Achmadi (Agrotechnology Study Program, Faculty of Agriculture, Wijaya Kusuma Surabaya University, 2024)
The weed known as